Design and characteristics of large displacement optical fiber switch - Bhuiyan, Moinul; Haga, Yoichi; Esashi, Masayoshi (IEEE, 2005)
Plastic optical fiber (POF) is suitable for indoor local area network (LAN), for example, in-home or office networks, because of its flexibility and its ease of connection due to its relatively large core diameter. A 1 2 optical switch for indoor LAN using POF and a shape memory alloy (SMA) coil actuator with magnetic latches was successfully fabricated and tested. In this paper, the design concept and the characteristics of this switch are described. To achieve switching by the movement of a POF, large displacement is necessary because the core diameter is large (e.g., 0.486 mm). A SMA coil actuator is used for large displacement and a magnetic latching system is employed for fixing the position of the shifted POF. For this design, the insertion loss is 0.40 to 0.50 dB and crosstalk is more than 50 dB without index-matching oil. Switching speed is less than 0.5 s at a driving current of 80 mA. A cycling test was performed 1.4 million times at room temperature. Another optical fiber switch was fabricated and successfully actuated using plastic clad fiber (PCF). PCF also has a large core diameter (e.g., 0.20 mm) and optical switches using PCF will be useful for short distance networks between buildings.